2011
DOI: 10.1007/s11814-010-0407-0
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and 3D simulation of slugging regime in a circulating fluidized bed

Abstract: A circulating fluidized bed (CFB) is widely applied in many industries because it has high efficiency. To develop and improve the process, an understanding of the hydrodynamics inside the CFB is very important. Computational fluid dynamics (CFD) represents a powerful tool for helping to understand the phenomena involved in the process. In this study, a CFD model was developed to represent a cold model of the laboratory scale CFB which was designed to study the hydrodynamics of a CFB using commercial CFD softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…4 illustrates a typical velocity vector field obtained for the 750‐g bed of 2900‐µm spherical particles at superficial air velocity of 2 m s −1 . Understanding of the velocity profile of particles in an SFB may be a useful tool in designing and operating an efficient fluidization system 8. Despite their importance, experimental studies on particle velocity in SFBs are scarce.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 illustrates a typical velocity vector field obtained for the 750‐g bed of 2900‐µm spherical particles at superficial air velocity of 2 m s −1 . Understanding of the velocity profile of particles in an SFB may be a useful tool in designing and operating an efficient fluidization system 8. Despite their importance, experimental studies on particle velocity in SFBs are scarce.…”
Section: Resultsmentioning
confidence: 99%
“…5 a, it is shown that the highest particle velocity occurred near the cone or midway between the cone and the bed column wall. However, different patterns of velocity profile could be obtained depending on the superficial air velocity 7–10. Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The known conventional beds are centrifugal fluidized beds, circulating fluidized beds, vibro-fluidized beds, tapered fluidized beds, spouted fluidized beds, etc. (Amornsirirat et al, 2011). The fluidized beds are being used in combustion, gasification, drying, heating and catalytic cracking, surface treatment, surface coating, gas separation, mass transfer, etc.…”
Section: Introductionmentioning
confidence: 99%